Punishing the Non-convicted Through Disclosure of Police Records - Maurutto, Paula (The British journal of criminology, 2023)
As police records expand with big data analytics, so too has the range of non-conviction information seeping into the public domain through criminal background checks. Numerous studies have documented the negative effects of background checks for those with criminal convictions, but less understood are the effects of non-conviction records. We draw on 8 focus groups and 52 interviews to understand how the release of non-conviction records are: (1) creating new institutional risk management pressures for police institutions, (2) expanding the role of employers as arbiters of risk, (3) redefining understandings of ‘the risky subject’ to include victims, those with mental health challenges and other innocent individuals subject to police contact and (4) raising critical legal questions about privacy and presumptions of innocence.